Pengaruh gaya kepemimpinan dan disiplin kerja terhadap kinerja pegawai pada Dinas Pendidikan Provinsi Jambi - Maharani, Andezsa Puan; Sumarni, Sumarni; Willian , Rohman (Jurnal Dinamika Manajemen, 2021)
This study entitled "The Influence of Leadership Style and Work Discipline on Employee Performance at the Jambi Provincial Education Office." The objectives of this study are as follows: (1) To see an illustration of the effect of performance, leadership style and work discipline at the Jambi Provincial Education Office. (2) To find out how much influence the leadership style has on employee performance at the Jambi Provincial Education Office. (3) To find out how much influence work discipline has on employee performance at the Jambi Provincial Education Office. (4) To find out how much influence the leadership style and work discipline have on employee performance at the Jambi Provincial Education Office. Based on the results of the research that (1) the overall picture of the total score of leadership styles which is included in the high category. the overall total score obtained has gone to the work discipline characteristic category which is included in the high category. the overall total score obtained has led to the employee performance category, including in the high category. (2) Based on the partial test results, leadership style has a significant effect on employee performance(3) Based on the partial test results, work discipline variables have a significant effect on employee performance. (4) The variables of leadership style and work discipline together have a significant effect on employee performance.